Modular irregularity strength of graphs - Martin Baca; Kadarkarai Muthugurupackiam; KM. Kathiresan; S. Ramya (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2020)
We introduce a modular irregularity strength of graphs as modification of the well-known irregularity strength. We obtain some estimation on modular irregularity strength and determine the exact values of this parameter for five families of graphs.